Analyzing Aviation Safety Trends in Nepal over the Past Fourteen Years (NPRC Journal of Multidisciplinary Research, 2025)
Background: Aviation industry have become crucial for economic development and connectivity but is still prone to risk. This can be evidenced by the series of accidents that have occurred in past few years. In the remote areas with limited road access, aviation is often the primary means of transportation for people and goods. The Civil Aviation Authority of Nepal (CAAN) is responsible for regulating aviation sector and has introduced various safety measures to improve aviation standards.Methodology: This study presents the data regarding aircrafts accidents that occurred in Nepal from 2010 A.D. to 2023 A.D. The data were collected from the official reports prepared by the Civil Aviation Authority of Nepal (CAAN) which is the civil aviation regulator of Nepal. The study categorizes the accidents based on aircrafts also that is, airplanes and helicopters. To understand more clearly graphical representation including bar graphs and tables are used.Results: The analysis shows that the majority of accidents resulted in 100% fatalities. The declining trend in aviation fatalities from 2010 to 2021 was interrupted by the two major incidents in 2022 and 2023, resulting in 22 and 17 deaths respectively. The drop of flight movements on year 2020 and 2021 played a significant role in making these two years’ incident free air in aviation industry.Conclusion: The study concludes that despite of decrease in fatalities in 2010 to 2021, the major accidents in 2022 and 2023 show that aviation risk exists. This highlights the need for better safety measures and rules, especially for tough weather and terrains.Novelty: Analyzing 14 years of aviation accidents in Nepal, highlighting safety trends, and using statistical and graphical methods to emphasize the need for better preventive measures is the novelty.